KEKUATAN KETERANGAN AHLI DALAM PEMBUKTIAN TINDAK PIDANA PEMBUNUHAN (Studi Kasus Putusan Nomor 777/Pid.B/2016/PN.JKT.PST Atas Nama Terdakwa Jessika Kumala Wongso) - Daniel Af Hutapea; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Justice is the responsibility of all law enforcement personnel, especially police, prosecutors and judges. Evidence is a problem that plays a role in the process of examining the trial. If the evidence proved by the law is